CYCLIC CURRENT-VOLTAGE CHARACTERISTICS OF A BILAYER LIPID MEMBRANE IN THE PRESENCE OF PORPHYRIN - Arakelyan, V.B.; Torosyan, A.L.; Ghazaryan, R.K. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2014)
The influence of Co-metalloporphyrins on electrical parameters of planar bilayer lipid membranes (BLM) has been investigated. The cyclic currentvoltage characteristics (CVC) of BLM have been measured both in the absence and presence of porphyrin in the solution surrounding the membrane. Based on the measured cyclic current-voltage characteristics the specific conductivity and capacity of BLM were calculated. In the presence of porphyrins the conductivity and capacity of BLM were shown to be increased.